Impact of climate change and bioenergy on nutrition - Cohen, Marc J.; Tirado, Cristina; Aberman, Noora-Lisa; Thompson, Brian (International Food Policy Research Institute, 2008)
Food security has deteriorated since 1995 and reductions in child malnutrition are proceeding too slowly to meet the Millennium Development Goal (MDG) target for halving hunger by 2015. Three major challenges threaten to drastically complicate efforts to overcome food insecurity and malnutrition: climate change, the growing use of food crops as a source of fuel and soaring food prices. Food security has four dimensions: food availability, access to food, stability of supply and access and safe and healthy food utilization. It is a key factor in good nutrition, along with health, sanitation and care practices. Globally, one billion people are currently without access to safe water and over 2 billion lack adequate sanitation facilities. Present global food supplies are more than adequate to provide everyone with all the needed calories, if the food were equally distributed. But over 820 million people in developing countries have calorie-deficient diets; over 60 percent live in Sub-Saharan Africa and South Asia.